IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY BERDASARKAN KONSEP TRI HITA KARANA PADA KOPERASI - Made Deny Claudia Larasati; Ketut Tanti Kustina (Valid: Jurnal Ilmiah, 2019)
The purpose of this study was to determine the implementation of Corporate Social Responsibility (CSR) based on the concept of Tri Hita Karana (THK) at KSU. Kori Amerta Sedana. This study uses a qualitative approach with a case study method. Sources of data from this study, namely primary and secondary data sources in the form of interviews and documentation from cooperatives. Therefore, in this study, researchers themselves or assisted by others were the main data collection tools. In this study there were informants, namely CSR actors at KSU. Kori Amerta Sedana and other related informants. Data collection is done by interviews, non-participant observation, and documentation. The results of this study indicate that the implementation of CSR in KSU. Kori Amerta Sedana has been carried out in an integrated manner and there are 3 (three) main references related to the implementation of CSR based on the THK concept, namely CSR parhyangan, CSR pawongan, CSR palemahan.